2019
DOI: 10.1002/solr.201900127
|View full text |Cite
|
Sign up to set email alerts
|

High‐Quality Single‐Mode Lasers Based on Zero‐Dimensional Cesium Lead Halide Perovskites

Abstract: Zero-dimensional (0D) perovskites are emerging as a class of optoelectronic materials due to their unprecedented strong excitonic properties and high stability. Although the photoluminescence properties of 0D perovskites (Cs 4 PbX 6 ) are investigated, the origin of green emission is still opaque, and their lasing performances are not reported. Herein, using the femtosecond transient absorption measurements to study the photophysical properties of Cs 4 PbBr 6 , the presence of polarons in Cs 4 PbBr 6 is reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…For example, the excited-state dynamics were investigated by femtosecond transient absorption measurements. [54] The stable energy of photoinduced bleach was 2.44 eV of Cs 4 PbBr 6 . A broad positive band below the bandgap was observed due to polaron absorption, illustrating the polaronic states of Cs 4 PbBr 6 .…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, the excited-state dynamics were investigated by femtosecond transient absorption measurements. [54] The stable energy of photoinduced bleach was 2.44 eV of Cs 4 PbBr 6 . A broad positive band below the bandgap was observed due to polaron absorption, illustrating the polaronic states of Cs 4 PbBr 6 .…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 94%
“…[47][48][49][50][51][52][53] On the other hand, the self-trapped exciton indicated a bound electron-hole pair trapped via strong electron/holelattice coupling, possibly leading to the formation of a polaron in the lattice distortion filed. [34,49,54] The self-trapped exciton has been confirmed in a variety of characterization technologies. For example, the excited-state dynamics were investigated by femtosecond transient absorption measurements.…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 96%
“…Unfortunately, the optical gain of QDs are always limited by the nonradiative biexciton (multicarrier) Auger recombination, [45] which is especially severe as the excitation intensity becomes higher. Unfortunately, the optical gain of QDs are always limited by the nonradiative biexciton (multicarrier) Auger recombination, [45] which is especially severe as the excitation intensity becomes higher.…”
mentioning
confidence: 99%
“…In general, for the potential application in stimulated emission, such as ASE and lasing, the characteristic of optical gain from laser medium is extremely important. Unfortunately, the optical gain of QDs are always limited by the nonradiative biexciton (multicarrier) Auger recombination, which is especially severe as the excitation intensity becomes higher. If extra carriers exist, the energy released during electron–hole recombination could be nonradiatively transferred to it, rather than contribute to the generation of photon.…”
mentioning
confidence: 99%
“…Development of perovskite lasers that can sustain for longer times has attracted attention. [ 144–146 ] New perovskites with better temperature and moisture stability have been employed to improve the laser stability. By using all‐inorganic perovskites which exhibit better stability, Eaton et al demonstrated single‐crystal CsPbX 3 nanowire lasers with improved stability.…”
Section: Stability Of Optically Pumped Perovskites Light Sourcesmentioning
confidence: 99%